Do People With Coronary Heart Disease Desire More Physical Activity and Advice From Their General Practitioners in This Regard? A German Cross-Sectional Population Survey (OptiCor Study) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Physical activity (PA) is important in coronary heart disease (CHD) management. General practitioners (GPs) can support CHD patients in improving their PA behaviour by offering advice on PA. However, it remains unclear whether people with CHD actually desire to increase their PA or to receive GP advice on this topic. This study explores the prevalence of these preferences and associations with person characteristics in the population of Germany.Methods: We conducted a nationwide, face-to-face cross-sectional survey of 1,119 individuals (≥35 years) with self-reported CHD, assessing their desire (1) to increase PA and (2) to receive GP advice on PA. Logistic regression models were used to examine associations between these preferences and person characteristics including age, gender, educational level, household income, migration background, residential region, PA level, and body mass index. For outcome (2), desire to increase PA was included as an additional covariate. Results: Overall, 44.0% (95% confidence interval (CI) = 41.1–46.9) expressed a desire to be more or more regularly physically active, while 51.0% (95% CI = 48.1–54.0) did not (no response: 5.0%). Higher (vs lower) education (odds ratio (OR) = 1.48; 95% CI = 1.09–2.01), higher (vs lower) income (OR = 1.21; 95% CI = 1.05–1.39), and urban (vs rural) residence (OR = 1.81; 95% CI = 1.28–2.57) were associated with a greater likelihood of desiring more PA.A desire for GP advice on PA was reported by 27.9% (95% CI = 25.3–30.6), while 71.2% (95% CI = 68.5–73.8) did not (no response: 0.9%). Medium (OR = 1.58; 95% CI = 1.17–2.15) and higher (vs lower) educational level (OR = 1.49; 95% CI = 1.06–2.08), urban (vs rural) residence (OR = 1.77; 95% CI = 1.22–2.57), and a desire (vs no desire) for more PA (OR = 3.36; 95% CI = 2.54–4.46) were associated with a greater likelihood of desiring GP advice on PA.Conclusion: Almost half of people with CHD in Germany desire to be more or more regularly physically active. About one third wish to receive GP advice on this topic. Some groups – particularly those who already wish to be more active – express the desire for GP advice on PA significantly more often. PA should be proactively addressed not only in GP consultations, but also in other healthcare settings.Support/Funding Source: German Ministry of Education and Research (01GY2103).